IMPLEMENTASI COUNTER-TRAFFICKING INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENANGGULANGI PERDAGANGAN MANUSIA DI INDONESIA TAHUN 2007-2013 - Puspahapsari, Adiningrum; Utomo, Tri Cahyo; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
In human trafficking, Indonesia as a country not only act as asource, but also a transit and a destination. The number of humantrafficking cases have been increasing since Indian Ocean tsunamioccured. According to Trafficking in Persons (TIP), Indonesia’sposition is at Tier 2, meaning that Indonesia governement has notmet the minimum standards of Trafficking Victims Protection Act(TVPA), but still showing some efforts to meet the standards. Tocombat human trafficking, Indonesia has cooperated with IOMthrough one of its law enforcement body, Indonesian National Police(INP). This research aims to analyze the cause of the increasingnumber of human trafficking cases although several IOM’s countertraffickingefforts have been placed throughout 2007-2013 period.This research employs theory of international cooperation andinternational organization with neoliberalism paradigm to analyzethe data collected through literature studies, documentation, andinterview as well. The result shows that the ineffectiveimplementation of IOM’s counter-trafficking efforts was notnecessarily caused by the abscence of mutual interests, but by theinavailability of quick feedback to deal with the constraints occuringduring the cooperation.